Clinical variations observed among the main hemoparasitosis caused by Rhipicephalus sanguineus in dogs - Albuquerque, Felipe Arnaud Sampaio Alencar de (2021)
Hemoparasitosis are diseases of great importance in the practice of a small animal’s veterinarian, due to their high number of cases in the clinical routine of these species, and the wide occurrence of their vectors. Related to hemoparasitosis in dogs, the tick Rhipicephalus sanguineus has the greatest importance due to parasitizing dogs, perpetuating hemoparasitosis in this host group. The present work describes a literature review about the three main hemoparasitosis in the routine of a veterinarian in Brazil, ehrlichiosis, caused by Ehrlichia canis, babesiosis caused by the protozoa Babesia canis and Babesia gibsoni, and anaplasmosis caused by Anaplasma platys, comparing them regarding the differences between clinical signs and laboratory alterations, such as the different types of anemia caused by these conditions that culminate in clinical signs related to them. It also aims to describe the similarity in the diagnostic techniques used and infection treatments, which in all cases is used tetracycline, the most commonly used is doxycycline, and highlight the need for further studies about this topic.